Evaluation of early marginal bone loss around posterior dental implants placed in axial and non-axial positions: a retrospective cone beam computed tomography (CBCT) analysis - Sruthima Gottumukkala Naga Venkata Satya; Duddukuri Murali Krishna; Penmetsa Gautami S.; Satyanarayana Raju Mantena; Venkata Ramesh Konathala Santosh; Mohan Kumar Pasupuleti; valli Veluri Sathya (EDP Sciences, 2024)
Introduction: To retrospectively assess the mesio-distal angular deviation/inclination of single implants restored in the posterior edentulous arches and evaluate the effect of angular deviations on the early bone loss after 12 months of functional implant loading. Materials and methods: This retrospective Cone beam computed tomography (CBCT) analysis assessed 60 single implants including 36 axially placed (AX Group) and 24 non-axially (NAX Group) placed implants of dimension 4.2 × 10 mm. Marginal bone loss (Mesial, Distal) was assessed at 1 year post implant loading in both maxillary and mandibular implants. Independent sample t-test was done for intergroup comparison and paired t-test for intragroup comparisons. Results: Mean MBL was significantly greater (P-0.02) in NAX group compared to AX group on both mesial and distal sides. Maxillary implants showed greater MBL (3.17 ± 1.33, 2.99 ± 1.63 on mesial and distal sides respectively) compared to mandibular implants (1.86 ± 0.53, 2.29 ± 0.90 on mesial and distal sides respectively). Conclusion: Greater mean MBL during first year of functional loading in NAX group and maxillary implants was observed with minimal post-operative complications and good survival rate in both groups.